Strategi Public Relations melalui Pengelolaan Media Sosial Instagram @pu_bpsdm oleh BPSDM Kementerian Pekerjaan Umum - Fariq Hasril Adiwardana; Hadiyanto Hadiyanto (Jurnal Riset Rumpun Seni, Desain dan Media, 2026)
Social media has become an important element in the public relations strategy of government agencies, including the Human Resources Development Agency (BPSDM) of the Ministry of Public Works (PU). Instagram, as the most popular platform in the world, plays a strategic role in disseminating institutional information. This study focuses on analyzing the PR strategy of BPSDM PU through the management of the Instagram account @pu_bpsdm. The method used is descriptive qualitative through observation, interviews with the Public Communication Team, and literature study. The results of the study show that the PR strategy is implemented through four step according to Cutlip & Center, namely situation analysis, planning, communication implementation, and evaluation. Issue identification is carried out through a top-down and bottom-up approach to ensure that the message is in line with public needs and the agency's agenda. Content production is carried out in a structured manner with a multi-layered verification mechanism, while routine evaluations show a significant increase in engagement from 25.2% (June), 29.28% (July), to 40.84% (August). These findings confirm that the BPSDM PU's digital PR strategy is effective and contributes to strengthening the institution's image in the public communication sphere.